Play the Brazilian way the secret skills of the world's greatest footballers - Clifford, Simon (Boxtree, 1999)
An explanation of the training methods through which Brazilian footballers develop their renowned skill and athleticism. The book includes a guide to Brazil's version of the five-a-side game, played with a special ball, which the author has introduced to young English players via regional schools.